Genetic cargo in the population of Kazakhstan according to the information-analytical system «Umit» - Gulshara Abildinova; Dina Zhanatayeva; Almagul Nagymtayeva (National Scientific Medical Center, 2017)
Purpose: to study of the frequency and structure of congenital and hereditary pathology according to the information-analytical database of congenital malformations and hereditary diseases. Methods: pregnant at risk groups, newborns, children, adults and families with isolated and multiple developmental defects, hereditary metabolic disorders, as well as couples suﬀering from infertility and miscarriage. The diagnosis was verifed using modern genetic methods (G-banding, FISH-method, RFLP, MLPA, mass spectrometric and ﬂuorimetric, cytogenetic methods). Results: according to the data of the genetic register, 36% (1446) of strict accounting were prevailing in the structure of pathologies, chromosome pathology-28% (1129), aneuploidy prevailed 97% (1013), 22% (869) of monogenic pathology with autosomal recessive type inheritance was 52% (456), autosomal dominant inheritance type 32% (283), X-linked inheritance type 26% (130). In addition, the congenital and hereditary pathology in the prenatal period is recorded; the share was 16% (630). In the structure of prenatal and postnatal pathology, Down syndrome predominated 62.7% (625). Conclusion: Thus, the formation of a database of congenital and hereditary pathologies with full coverage of all newborns, children, fetuses, comprehensive examination of families and clarifcation of the diagnosis, allows establishing the frequency, structure of congenital malformations and hereditary pathology.